1482 Paediatric Trauma Transfers: Are we Fast Enough?. (October 2012) - Cooper, N; Parkins, K; Grainger, D
Abstract : Background: Children with traumatic brain injury (TBI) require rapid stabilisation and transfer to a paediatric multi-trauma centre (pMTC) within 3 hours (4 hours if rural) of injury (UK guidelines 2010). In our region transfer of children is either by local hospital team or regional paediatric transport service (NWTS started November 2010). Methods: Retrospective 16 month audit patients with TBI transferred into 2 regional pMTCs, identifying severity of injury, areas of delay, length of stay (LOS) on PIC and survival to hospital discharge. Results: 56 patients with TBI were identified. Median time of arrival at pMTC 355 minutes (IQR260–495), 210 minutes for time critical injuries (IQR180–270). Areas of delay identified: Referral time post injury - median 115 minutes (IQR90–172) Insertion of invasive lines e.g. arterial or central in 54% Neurosurgical Intervention at adult MTC in 4 patients Local team vs NWTS= 210 vs 431 minutes Patients: transferred by NWTS were more likely to have severe head injury and multi-trauma. However, median LOS was similar (local team 3.5 (IQR 2–10) vs NWTS 3 (IQR 1–6) days). Overall mortality rate was 6% (national mortality = 10%). Conclusions: Transfer children with TBI within 3–4 hour national target remains challenging. However, regional LOS and mortality rate remain low. This audit highlights the need for early referral, in line with the recent Trauma Network guidelines. The use of peripheral or intraosseous line(s) and full non-invasive monitoring, ensuring patients are well oxygenated and have an adequate BP may also improve transfer times.